Study of FRP Ship Waste Composite Materials and Its Combustion Residue - Rahmawati, Nabila; Novita, Yopi; Komarudin, Didin; Iskandar, Mokhamad Dahri (International Journal of Marine Engineering Innovation and Research, 2024)
The escalating utilization of FRP materials ultimately gives rise to issues related to waste production. Waste disposal typically involves incineration, as practiced at UD Wahyu Asih Fiberglass. The combustion process yields thick black smoke and a pungent odor. Incineration does not annihilate fiberglass material but generates combustion byproducts, such as solid ash. This study aims to elucidate the material type, chemical element content, and associated properties inherent in FRP shipbuilding materials at UD Wahyu Asih Fiberglass Shipyard. The methodology commences with the identification of materials utilized in FRP ship manufacture through field observations at the shipyard. Another objective of this study is to quantify the ash content and ascertain the total particulate matter during the incineration process of FRP shipbuilding material waste via laboratory tests. The total particulate data obtained will be compared with applicable emission quality standards.